Electron Spin Resonance and Atomic Force Microscopy Study on Gadolinium Doped Ceria - Cesare Oliva; Francesco Orsini; Serena Cappelli; Paolo Arosio; Mattia Allieta; Mauro Coduri; Marco Scavini (Journal of Spectroscopy)
A combined electron spin resonance (ESR) and atomic force microscopy (AFM) study on Ce1−xGdxO2−x/2 samples is here presented, aimed at investigating the evolution of the ESR spectral shape as a function of x in a wide composition range. At low x=0.02, the spectrum is composed of features at geff≈2; 2.8; 6. With increasing x, this pattern merges into a single geff≈2 broad ESR curve, which assumes a Dysonian-shaped profile at x≥0.5, whereas, at these x values, AFM measurements show an increasing surface roughness. It is suggested that the last could cause the formation of surface polaritons at the origin of the particular ESR spectral profile observed at these high Gd doping levels.